The analysis and competition strategy of the uncrowned king of badminton Lee Chong Wei’s key points - Ma, Shuzhen; Soh, Kim Geok; Japar, Salimah Binti; ., Yang; Xu, Yanqi (Informa UK Limited, 2024)
The skill and tactical application of key stages of badminton usually show a decisive impact on the competition results. In this research, the skill and tactical performances of Lee Chong Wei in 10 representative matches of the Olympic Games, World Championships and Open in the Quarter, Quarter and Final, respectively, were selected for study. A one-way ANOVA with paired samples t-test was used to analyze the differences of their relevant skill parameters between the ace-shot and misses. Lee Chong Wei is accustomed to serving backhand nets and uses lift shot skills when receiving serves for the first shot on key points, while the mainstream skill of the second shot is drop shot, resulting poor lift shot effect. Furthermore, the multi-shot skill is mainly used to hit the opponent’s forecourt backhand area, and the lift shot skill is conducive to scoring, while the picking skill is ineffective.